Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan melalui Manajemen Berbasis Sekolah - Miman Abdurahman; Hilam Farouq Ghoer (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2022)
The purpose of this study is to improve the quality of education in schools, namely by paying attention to all aspects in a school, both inputs, processes, and outputs. The success of a school will only be able to be carried out through effective management, as well as optimal leadership roles of the principal. The research method used is comparative descriptive qualitative research. Data collection is obtained from information, places and activities of the principal's leadership activities, as well as documents. Data collection techniques include in-depth interviews, direct observation, and recording documents. The data validity test is carried out by applying source trianggulation, method trianggulation. The results of the study are in the form of main findings, namely: 1) The Role of the Principal in Planning, Implementation and Evaluation in an effort to improve the quality of education in schools 2) Improving the quality of schools is determined by the leadership role of the principal in carrying out hisduties and functions. 3) Overall, the leadership role of the principal of SMP Negeri 1 Sukaresmi and SMP Fauzaniyyah, Garut Regency in carrying out their leadership role as principal through school-based management has been running well, but in terms of planning, organizing, implementing, supervising and evaluating it has not run optimally.